Much to be done: towards an effective transitional justice model for dealing with conflict-related crimes of sexual and gender-based violence - Mazimhaka, Anne P Inturire (Department of Public Law, 2014)
Many countries in Africa have experienced conflicts characterized by gross human rights violations, including widespread and systematic sexual and gender-based violence. Several of these are currently grappling with the difficult issue of addressing the wrongs of the past while at the same time trying to secure a stable and democratic future. This study considers what an appropriate model of transitional justice should be in the African context, particularly as pertains to crimes of sexual and gender-based violence. This chapter will briefly illustrate the prevalence of sexual and gender-based violence in conflict situations, particularly in Rwanda, note the legal developments made thus far, and establish the aim of this particular study.